Distribution of interstitial cells of Cajal and nerve fibers in rat stomach in streptozotocin-nicotinamide-induced diabetes mellitus - Veličkov, Aleksandra I.; Petrović, Vladimir; Djordjević, Branka; Veličkov, Asen V.; Petrović, Aleksandar; Lazarević, Milica; Cvetković, Julija (Archives of Biological Sciences, 2023)
Paper description: Regulation of peristalsis is a complex process involving interstitial cells of Cajal (ICCs). There is no data on ICC distribution in the stomach in diabetes mellitus type 2 (DMT2). Data provide insight into the role of ICCs in diabetic gastro enteropathy. The research was focused on morphological and numerical changes in different ICC subtypes in the streptozotocin-nicotinamide (STZ-NA)-induced DMT2 rat model. Changes in all ICC types without nerve structure disorders were observed in contrast to animal models described in the literature in DMT1. These results contribute to the understanding of the mechanism and chronology of gastric motility disorders in diabetes. Abstract: Diabetic peristalsis disorders are common complications in diabetes mellitus type 2. Disturbance of interstitial cells of Cajal (ICC) caused by metabolic changes in diabetes could explain the symptoms of diabetic gastroenteropathy. Although heterogenous interstitial cell types represent only 5% of the cell population of the muscle layer in the gastrointestinal tract (GIT), they are important for conducting electrical signals and regulating muscle excitability. The aim of this study was to investigate the alterations of the myenteric and intramuscular ICCs in the gaster of rats with diabetes mellitus type 2 (DMT2), as well as determine their distribution in relation to smooth muscle cells and enteric nerve structures. Male Wistar rats were used and DT2 was induced by streptozotocin-nicotinamide (STZ-NA) application. The stomach specimens were exposed to type III transmembrane tyrosine kinase (c-KIT), neurofilament (NF-M) protein and desmin antibodies to investigate the ICC, enteric neurons and smooth muscle cells. Morphological changes of the cells were quantified by the numerical areal density of intramuscular ICC, the ICC score of myenteric ICC and the volume density of nerve fibers. In conclusion, a statistically significant decrease in the number of intramuscular ICC and myenteric ICC without nerve fiber loss were observed in all stomach regions in rats with STZ-NA-induced DMT2.